Perceptual study on conventional quality of life indicators - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah; Rosli, Nur Farhanah; Abdullah, Muhammad Faris (Malaysia Institute of Planner, 2018)
Quality of life (QOL) is both individual and collective attributes. Quality of life should encompass both objective and subjective measures whilst promoting for balance in every aspect of human existence. The objective of this study is to assess the QOL of the population in Malaysia by using Selangor as a case study. 600 samples from four districts in Selangor were selected through random sampling method. From literature review, 9 main components of QOL were identified and included in questionnaire form. Relative importance index (RII) equation was then used to report on the analysis of QOL components. Results from the survey indicated that majority of the respondents were likely to perceive QOL components as moderate and highly satisfied. Overall, respondents claimed that they were satisfied and enjoying their lives and at the same time satisfied with their current quality of life. The results indirectly show that each of QOL component was interrelated with each other in creating the satisfaction on quality of life of the people. This is in line with the findings on the three basic human relationships with Allah SWT, with other human and with nature in protecting their faith (din), human self (nafs), intellect ('aql), posterity (nasl) and wealth (mal) through establishing justice, eliminating prejudice and alleviating hardship by promoting good and preventing harm to self and others.